PENGETAHUAN IBU TENTANG DEMAM BERDARAH DENGUE DENGAN KEBERADAAN JENTIK DI DUSUN KLEDOKAN, SELOMARTANI, KALASAN, SLEMAN, YOGYAKARTA - Patria Asda; Sri Sumartina (STIKES Wira Husada Yogyakarta, 2018)
ABSTRACT Background: The results of a preliminary study by interviews with the head space conducted by researchers at the health center Kalasan on October 6, 2015, found the number of people suffering from dengue from January to March 2015 as many as 27 people and one family there are two persons affected by the disease DBD.Objective: To identify level of knowledge about dengue haemoraghic fever in dusun kledokan, selomartani, Kalasan, Sleman, Yogyakarta. Methods: This study used quantitative methods of observational analyticwith cross sectional design. Sample in this research are PKK members in RT 4-6 Dusun Kledokan, Selomartani, Kalasan. Research tool used is a questionnaire for the level of knowledge and observation sheet for the existence of larva, engineering analysis using Chi Square (x2).Results: The level of knowledge of DBD on PKK members in RT 4-6 Dusun Kledoakan, Selomartani, Kalasan in both categories 82 respondents(92.1%), while the presence of larvae were classiﬁ ed as no larvae namely 62 respondents(69.7%). The results of research that is no relationship between the level of knowledge of DHF in PKK with the existence of larva with ƿ-value = 0.001 <0.05. Conclusion: Based on the results that the relationship between the level of knowledge of DHF in PKK with the existence of larva in Hamlet Kledokan, Selomartani, Kalasan, Sleman, Yogyakarta.